PFAS in a Swedish wastewater treatment plant : An analysis of the effectiveness of major treatment steps on 33 PFAS - Forsberg, Jonatan (Luleå tekniska universitet, Institutionen för samhällsbyggnad och naturresurser, 2022)
Wastewater treatment plants (WWTP) are known spreaders of per- and polyfluoroalkyl substances (PFAS) into the environment. Luleå University of Technology is conducting a yearlong study in which PFAS concentrations in the different treatment steps are measured at Uddebo treatment plant. This report covers the first four months of the year-long study. The aims of this study are to see what happens with the PFAS concentrations in the treatment processes, if they are above regulated limits, and to see if concentrations at Uddebo are comparable toreference concentrations in Sweden. Sampled PFAS concentrations were taken once per fortnight in incoming wastewater, after primary sedimentation, after Moving Bed Biofilm Reactor (MBBR), after secondary sedimentation and after the pilot treatment plant containing granulated active carbon (GAC) filter when it was in use. Precursors in incoming wastewater and PFAS in sludge were measured in samples taken once per month. Comparing the 33 analysed PFAS in wastewater at each sampling point, 30 analysed precursors for PFAS in incoming wastewater and 30 analysed PFAS in sludge, only PFOS and PFOA wereregularly found in both wastewater and in outgoing sludge. This indicates a separation of PFAS in the different medium, with sludge having PFAS where the perfluorinated carbon chain length is grater than 6. Out of the analysed 33 PFAS in wastewater PFOA had the highest median concentration of about 7 ng/l with no significant variation between the wastewater sample points. Similarly, the median concentration of total detected 33 PFAS was around 35 ng/l with no significant variation between the wastewater sample points, indicating no significant treatment of measured PFAS during WWTP. This was also comparable to other WWTP in Sweden. PFBA, PFHxA and PFPeA precursors had the highest concentration of the measured 30 PFAS precursors, however, except for one sampling occasion, no significant deviation in precursor PFAS could be detected during the sampling period. Out of the 30 analysed ...